Biomolecules from snail mucus (Helix aspersa) conjugated gold nanoparticles, exhibiting potential wound healing and anti-inflammatory activity. Issue 48 (23rd November 2020) - Gubitosa, Jennifer; Rizzi, Vito; Fini, Paola; Laurenzana, Anna; Fibbi, Gabriella; Veiga-Villauriz, Clara; Fanelli, Fiorenza; Fracassi, Francesco; Onzo, Alberto; Bianco, Giuliana; Gaeta, Carmine; Guerrieri, Antonio; et al.
Abstract : In this work, for the first time, snail slime from garden snails " Helix Aspersa Müller ", has been used to induce the formation of eco-friendly gold nanoparticles (AuNPs-SS) suitable for biomedical applications. Abstract : In this work, for the first time, snail slime from garden snails " Helix Aspersa Müller ", has been used to induce the formation of eco-friendly gold nanoparticles (AuNPs-SS) suitable for biomedical applications. An AuNPs-SS comprehensive investigation was performed and AuNPs with an average particle size of 14 ± 6 nm were observed, stabilized by a slime snail-based organic layer. Indeed, as recognized in high-resolution MALDI-MS analyses, and corroborated by FESEM, UV-Vis, ATR-FTIR, and XPS results, it was possible to assess the main presence of peptides and amino acids as the main components of the slime, that, combined with the AuNPs confers on them interesting properties. More specifically, we tested, in vitro, the AuNPs-SS safety in human keratinocytes and their potential effect on wound healing as well as their anti-inflammatory properties in murine macrophages. Moreover, the AuNPs-SS treatment resulted in a significant increase of the urokinase-type plasminogen activator receptor (uPAR), essential for keratinocyte adhesion, spreading, and migration, together with the reduction of LPS-induced IL1-β and IL-6 cytokine levels, and completely abrogated the synthesis of inducible nitric oxide synthase (iNOS).